1-year results after PCI with the COMBO stent in all-comers in Asia versus Europe: Geographical insights from the COMBO collaboration. (15th May 2020) - Chandrasekhar, Jaya; Kalkman, Deborah N.; Aquino, Melissa B.; Sartori, Samantha; Hájek, Petr; Atzev, Borislav; Hudec, Martin; Ong, Tiong Kiam; Mates, Martin; Borisov, Borislav; Warda, Hazem M.; den Heijer, Peter; et al.
Abstract: Background: The COMBO drug-eluting stent combines sirolimus-elution from a biodegradable polymer with an anti-CD34+ antibody coating for early endothelialization. Objective: We investigated for geographical differences in outcomes after percutaneous coronary intervention (PCI) with the COMBO stent among Asians and Europeans. Methods: The COMBO Collaboration is a pooled patient-level analysis of the MASCOT and REMEDEE registries of all-comers undergoing attempted COMBO stent PCI. The primary outcome was 1-year target lesion failure (TLF), composite of cardiac death, target vessel myocardial infarction (TV-MI) and target lesion revascularization (TLR). Results: This study included 604 Asians (17.9%) and 2775 Europeans (82.1%). Asians were younger and included fewer females, with a higher prevalence of diabetes mellitus but lower prevalence of other comorbidities than Europeans. Asians had a higher prevalence of ACC/AHA C type lesions and received longer stent lengths. More Asians than Europeans were discharged on clopidogrel (86.5% vs 62.8%) rather than potent P2Y12 inhibitors. One-year TLF occurred in 4.0% Asians and 4.1% of Europeans, p = 0.93. The incidence of cardiac death was higher in Asians (2.8% vs. 1.3%, p = 0.007) with similar rates of TV-MI (1.5% vs. 1.2%, p = 0.54) and definite stent thrombosis (0.3% vs. 0.5%, p = 0.84) and lower incidence of TLR than Europeans (1.0% vs. 2.5%, p = 0.025). After adjustment, differences for cardiac death and TLR were no longer significant. Conclusions: In the COMBO collaboration, although 1-year TLF was similar regardless of geography, Asians experienced higher rates of cardiac death and lower TLR than Europeans, while incidence of TV-MI and ST was similar in both regions. Adjusted differences did not reach statistical significance. Clinicaltrial.gov identifier-numbers: NCT01874002 (REMEDEE Registry), NCT02183454 (MASCOT registry). Highlights: The COMBO collaboration included 604 Asians (17.9%) and 2775 Europeans (82.1%). Asians were younger with higher prevalence of diabetes mellitus and C type lesions. More Asians than Europeans were discharged on clopidogrel (86.5% vs 62.8%) rather than potent P2Y12 inhibitors. One-year TLF occurred in 4.0% Asians and 4.1% of Europeans, p = 0.93. Asians experienced higher crude rates of cardiac death and lower TLR than Europeans.